Returning to emotional eating: the emotional eating scale psychometric properties and associations with body image flexibility and binge eating - Duarte, Cristiana (2015)
This study tests the Emotional Eating Scale (EES) psychometric properties and correlates, and the moderator effect of body image flexibility on the association between emotional eating and binge eating.